Exploiting the Anticancer, Antimicrobial and Antiviral Potential of Naphthoquinone Derivatives: Recent Advances and Future Prospects - Shouyan Xiang; Yubei Li; Shah Nawaz Khan; Weixin Zhang; Gaoyang Yuan; Jiahua Cui (Pharmaceuticals)
Cancer remains a primary cause of mortality, with over 18.1 million new cases and 9.6 million deaths globally in 2018. Chemotherapy, which utilizes a spectrum of cytotoxic drugs targeting the rapidly dividing cancer cells, is a predominant treatment modality. However, the tendency of chemotherapeutics to induce drug resistance and exhibit non-specific cytotoxicity necessitates the development of new anticancer agents with heightened efficacy and minimized toxicity. In recent years, the discovery of safe and effective antibacterial/antiviral agents has also been a hot spot in medicinal chemistry. This paper comprehensively reviews the synthesis, anticancer/antibacterial/antiviral activity, and structure–activity relationships of natural 1,4-naphthoquinones and their derivatives. It highlights their potential as efficient and low-toxicity antitumor and anti-infectious drug candidates.